Soluble Mediators From Lactobacillus rhamnosus Gorbach‐Goldin Support Intestinal Barrier Function in Rats After Massive Small‐Bowel Resection. Issue 6 (9th January 2018) - Wu, Jiang; Yang, Kefeng; Wu, Wenjie; Tang, Qingya; Zhong, Yan; Gross, Gabriele; Lambers, Tim T.; van Tol, Eric A. F.; Cai, Wei
Abstract: Background: Intestinal barrier plays an essential role in maintaining gastrointestinal health. This study aimed to explore the effects of a soluble mediator preparation derived from Lactobacillus rhamnosus Gorbach‐Goldin (LGG) on intestinal barrier function in a rat model of short bowel syndrome (SBS). Methods: Six‐week‐old male Sprague‐Dawley rats underwent 80% small‐bowel resection (SBR) and then were supplemented with water (SBS), 5 × 10 8 colony‐forming unit viable LGG (SBS+LGG), or the LGG soluble mediators (SBS+LSM) in an equivalent dose to LGG by intragastric gavage daily from day 2 throughout day 14 after operation. Rats that underwent bowel transection and reanastomosis were used as the sham group. Body weight, ileum histology, intestinal permeability and bacterial translocation, inflammatory cytokines, and tight junction protein expressions of ileum were evaluated. Results: Animals undergoing SBR showed higher intestinal permeability and decreased expression of tight junction proteins in the ileum than sham group. Both SBS+LGG and SBS+LSM groups had reduced bacterial translocation and intestinal permeability as compared with the SBS group, with lower levels of serum endotoxin and tumor necrotizing factor alpha in ileum tissues. Moreover, the SBS+LSM group showed better body weight gain, lower endotoxin and FD‐40 levels, and higher expressions of claudin‐1 and claudin‐4 in ileum than the SBS+LGG group. Conclusion: Enteral supplementation of LSMs or viable LGG can ameliorate intestinal barrier disruption in a rat model of SBS. The LSM preparation not only mimicked biological effects of viable LGG but also was revealed to be more effective in reducing inflammation and supporting intestinal barrier function.